Drought, freshwater availability and cultural resilience on Easter Island (SE Pacific) during the Little Ice Age. (May 2020) - Rull, Valentí
After decades of human-deterministic explanations for the collapse of the ancient Rapanui culture that inhabited Easter Island (Rapa Nui) before European contact (1722 CE), paleoecological studies developed over the last decade have provided sound evidence of climate changes and their potential socioecological impacts. Especially significant is the occurrence of a century-scale drought (1570–1720 CE) during the Little Ice Age (LIA). Freshwater is a critical resource on Easter Island that heavily depends on rain, which maintains the only three permanent surficial freshwater sources on the island: two lakes (Rano Kao and Rano Raraku) and a marsh (Rano Aroi). Under these conditions, the LIA drought could have significantly affected human life; however, the Rapanui society remained healthy, showing remarkable resilience. There are two main hypotheses on how the ancient Rapanui could have obtained freshwater to guarantee their continuity. One of these hypotheses proposes that Lake Kao was a permanent source of freshwater, even during the LIA drought, which led to some intraisland cultural and population reorganizations. The coastal groundwater hypothesis dismisses the use of lakes and other surficial freshwater sources to maintain the water-stressed Rapanui population and contends that the only routine freshwater sources during the LIA drought were the abundant and widespread coastal seeps fed by fresh/brackish groundwater. The pros and cons of these two hypotheses are discussed on the basis of the available archeological and paleoecological evidence, and it is concluded that given the present state of knowledge, neither can be rejected. Therefore, these two proposals could be complementary rather than mutually exclusive.